Negative nasopharyngeal swabs in COVID-19 pneumonia: the experience of an Italian Emergengy Department (Piacenza) during the first month of the Italian epidemic - Poggiali, Erika; Vercelli, Andrea; Vadacca, Giovanni Battista; Schiavo, Roberta; Mazzoni, Silvana; Ioannilli, Eva; Demichele, Elena; Magnacavallo, Andrea (Acta Biomedica Atenei Parmensis, 2020)
Coronavirus disease (COVID-19) is a systemic disease which can cause multiple organ failure and death primarly due to vascular endothelium injury. Severe acute respiratory distress syndrome (ARDS) is the main cause of death: its management and treatment should be tailored to the individual COVID-19 patient’s phenotype. Early diagnosis of COVID-19 is paramount for disease treatment and infection control. Naso-pharyngeal (NP) swab is commonly used as screening and diagnostic tool for COVID-19, but in some cases it can be resulted negative even in presence of clinical and epidemiological criteria, and typical radiological and laboratory findings of COVID-19, as we have observed. Here we report our experience in the first month of the Italian epidemic. We strongly recommend clinicians to maintain a high index of suspicion for COVID-19, regardless of the persistence negativity of NP swabs, and not to delay the initiation of therapy in presence of typical clinical, radiological and laboratory findings of COVID-19.